Private London [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Private novels., 2012)
For Hannah Shapiro, a beautiful young American student, a particular nightmare began eight years ago in Los Angeles, when Jack Morgan, owner of Private - the world's most exclusive detective agency - saved her from a horrific death. She has fled her country, but can't flee her past. The terror has followed her to London, and now it is down to former Royal Military Police Sergeant Dan Carter, head of Private London, to save her all over again.